Light-activated protein interaction with high spatial subcellular confinement - Benedetti, Lorena; Barentine, Andrew E. S.; Messa, Mirko; Wheeler, Heather; Bewersdorf, Joerg; De Camilli, Pietro (Proceedings of the National Academy of Sciences - PNAS, 2018)
Methods to acutely manipulate protein interactions at the subcellular level are powerful tools in cell biology. Several blue-light-dependent optical dimerization tools have been developed. In these systems one protein component of the dimer (the bait) is directed to a specific subcellular location, while the other component (the prey) is fused to the protein of interest. Upon illumination, binding of the prey to the bait results in its subcellular redistribution. Here, we compared and quantified the extent of light-dependent dimer occurrence in small, subcellular volumes controlled by three such tools: Cry2/CIB1, iLID, and Magnets. We show that both the location of the photoreceptor protein(s) in the dimer pair and its (their) switch-off kinetics determine the subcellular volume where dimer formation occurs and the amount of protein recruited in the illuminated volume. Efficient spatial confinement of dimer to the area of illumination is achieved when the photosensitive component of the dimerization pair is tethered to the membrane of intracellular compartments and when on and off kinetics are extremely fast, as achieved with iLID or Magnets. Magnets and the iLID variants with the fastest switch-off kinetics induce and maintain protein dimerization in the smallest volume, although this comes at the expense of the total amount of dimer. These findings highlight the distinct features of different optical dimerization systems and will be useful guides in the choice of tools for specific applications.